Conductivity and F-19 NMR in PbGeO3-PbF2-CdF2 glasses and glass-ceramics - Bueno, L. A.; Donoso, J. P.; Magon, C. J.; Kosacki, I; Filho, FAD; Tambelli, C. C.; Messaddeq, Younes [UNESP]; Ribeiro, SJL (Elsevier B.V., 2005)
The temperature dependence of the electrical conductivity and the F-19 nuclear magnetic resonance (NMR) of PbGeO3-PbF2CdF, glasses and glass ceramics are investigated. The measured conductivity values of the glasses are above 10(-5) Skin at 500 K, and increase with increasing lead fluoride content. Activation energies extracted from the conductivity data are in the range 0.59-0.73 eV. Results are consistent with the hypothesis that in these oxyfluoride glasses lead fluoride rich clusters are dispersed in a metagermanate based matrix providing increasing mobility pathways for conducting ions. The conductivity of a sample of the glass ceramic of composition (mol%) 60PbGeO(3-)20PbF(2)-20CdF(2) was found to be smaller than that in the corresponding glass, suggesting that there are poor ionic conducting regions in the interface between the nanometer sized crystals. The temperature dependence of the F-19 relaxation times, measured in the range 100-800 K, exhibit the qualitative features associated with high fluorine mobility in both, glass and glass ceramics materials. We suggest that de-convolution of the spin-lattice relaxation rates observed in the glass ceramics shows that the observed high temperature rate maximum is associated with the diffusional motions of the fluorine ions in beta-PbF2 crystals. (c) 2005 Elsevier B.V. All rights reserved.